Experimental evidence of size‐selective harvest and environmental stochasticity effects on population demography, fluctuations and non‐linearity. (19th February 2023) - Rogers, Luke A.; Moore, Zachary; Daigle, Abby; Luijckx, Pepijn; Krkošek, Martin
Abstract: Theory and analyses of fisheries data sets indicate that harvesting can alter population structure and destabilise non‐linear processes, which increases population fluctuations. We conducted a factorial experiment on the population dynamics of Daphnia magna in relation to size‐selective harvesting and stochasticity of food supply. Harvesting and stochasticity treatments both increased population fluctuations. Timeseries analysis indicated that fluctuations in control populations were non‐linear, and non‐linearity increased substantially in response to harvesting. Both harvesting and stochasticity induced population juvenescence, but harvesting did so via the depletion of adults, whereas stochasticity increased the abundance of juveniles. A fitted fisheries model indicated that harvesting shifted populations towards higher reproductive rates and larger‐magnitude damped oscillations that amplify demographic noise. These findings provide experimental evidence that harvesting increases the non‐linearity of population fluctuations and that both harvesting and stochasticity increase population variability and juvenescence. Abstract : A factorial experiment with treatments of environmental stochasticity and harvesting shows that both trigger population juvenescence and increase fluctuations. Harvesting causes an increase in non‐linearity of the population dynamics, and a fitted fisheries model suggests that harvesting increased population growth rates and shifted dynamics to higher amplitude damped oscillations that amplify demographic noise.